Special aspects of para-olympic athletes' sport activity in the process of self-education - V.V. Shuba (H.S. Skovoroda Kharkov National Pedagogical University, 2017)
Purpose: to determine and substantiate influence of self-education components of para-Olympic athletes' sport activity. Material: in the research 46 para-Olympic athletes form three teams of game kinds of sports participated: combined football, basketball and volleyball teams of Ukraine. The program of self-education process's organization was designed for 9 months and consisted of three stages. Pedagogic program consisted of 9 classes. Optimal time of one training session was 45 minutes a day (in total - 9 days). Results: we determined the need in consideration of athletes' individual-personality features in organization the self-education process. We also substantiated and experimentally tested correlations, which facilitate: adequate organization of athletes' self-education process; mastering of sport knowledge and skills of behavior in different extreme situations; realization of own potentials in sport and social life. Conclusions: the structure of athletes' self -education is presented by combination of interconnected components: motivation-personal (motives, demands, settings, moral-will qualities and individual personal features); cognitive (system of knowledge about oneself and sport functioning); activity (formation of skills in self cognition, self-organization and self-control).